EVALUATION OF PUBLIC POLICY IN THE EDUCATION SECTOR: HOW CAN PUBLIC ADMINISTRATION OPTIMISE THE USE OF EDUCATION FUNDS? - Zainuddin Zainuddin; Al-Amin (Adisam Publisher, 2025)
Public policy evaluation in the education sector plays an important role in ensuring the efficient and targeted use of education funds. This article discusses efforts to optimise state administration in managing the education budget through increased transparency and accountability, equitable distribution of funds, and collaboration between stakeholders. The study in this research uses the literature method. The results show that the implementation of a clear and accurate monitoring system, as well as the use of information technology, is crucial in minimising the potential for misuse of funds. In addition, the allocation of funds based on needs and appropriate priorities, especially in remote areas, will help achieve equality in education quality. Active participation from educational institutions and communities was also identified as an important factor to support the state administration in adjusting and refining policies, so that education funds can be maximally utilised to achieve national education goals.